How to relate models to reality? An epistemological framework for the validation and verification of computational models - Claudius Gräbner (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
Agent-based simulations have become increasingly prominent in various disciplines. This trend is to be appreciated, but it comes with challenges: while there are more and more standards for design, verification, validation, and presentation of the models, the various meta-theoretical strategies of how the models should be related to reality often remain implicit. Differences in the epistemological foundations of models makes it, however, difficult to relate distinct models to each other. This paper suggests an epistemological framework that helps to make explicit how one wishes to generate knowledge about reality by the means of one's model and that helps to relate models to each other. Because the interpretation of a model is strongly connected to the activities of model verification and validation, I embed these two activities into the framework and clarify their respective epistemological roles. Finally, I show how this meta-theoretical framework aligns well with recently proposed framework for model presentation and evaluation.
Keywords: 330; Agent-based modelling; epistemology; models; validation; verification